Clinical Integration of a Highly Accurate Polymerase Chain Reaction Point-of-Care Test Can Inform Immediate Treatment Decisions for Chlamydia, Gonorrhea, and Trichomonas. Issue 4 (24th April 2022) - Dawkins, Megan; Bishop, Lisa; Walker, Paula; Otmaskin, Danielle; Ying, Julia; Schmidt, Ryan; Harnett, Glenn; Abraham, Teresa; Gaydos, Charlotte A.; Schoolnik, Gary; DiBenedetto, Kevin
Abstract : A new point-of-care polymerase chain reaction device for chlamydia, gonorrhea, and trichomonas in less than 30 minutes can be integrated into clinical workflow with minimal impact on staff time and visit duration while potentially dramatically reducing overtreatment and undertreatment of these sexually transmitted infections. Supplemental digital content is available in the text. Abstract : Background: Accurate same-day sexually transmitted infection (STI) diagnostic testing is generally unavailable, leading to syndromic management with high rates of overtreatment and undertreatment. We analyzed the ease of integration of the Visby STI Panel into clinical practice, studied acceptance by patients and clinic personnel, and assessed the potential to inform accurate treatment decisions. Methods: In a cross-sectional single-visit study of 55 women aged 18 to 56 years, women self-collected vaginal swab samples that were analyzed using the Visby STI Panel for Chlamydi a trachomatis, Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV). Results were compared with standard-of-care clinic results from send-out laboratory polymerase chain reaction tests. Surveys assessed patient and device operator experiences with the Visby STI Panel and clinicians' perceived need for and acceptance of the device. Time parameters were measured to evaluate the impact on clinical workflow, and syndromic treatment decisions were compared with anticipated treatment based on the Visby STI Panel results. Results: Patients strongly agreed that sample self-collection was easy, and operators reported the device easy to use. Clinicians valued the rapid return of results, and patients were comfortable waiting up to 30 minutes to receive them. In 13 of 15 cases, the Visby STI Panel correctly identified undertreated patients as infected and correctly identified all 33 incidences of overtreatment. Conclusions: Clinical adoption of the Visby STI Panel into primary care clinics and doctors' offices could reduce overtreatment and undertreatment of STIs. If integrated efficiently into the clinical workflow, the test would have minimal impact on staff time and visit duration for patients.